Efektivitas Serai Wangi (Cymbopogon nardus) Untuk Mengendalikan Hama Kutu Beras (Sitophilus oryzae) - Muhammad Indar Pramudi Pramudi; Hawatul Zainap (www.ulm.ac.id, 2026)
Rice storage for long periods often faces pest problems, one of which is Sitophilus oryzae L., which causes weight loss, contamination by insects, and a decrease in the nutritional quality of rice. To overcome this, the use of vegetable pesticides is an environmentally friendly alternative. Botanical pesticides are natural compounds that come from plants and can act as repellents, attractants, antifertility and have toxic effects on pests. This study aims to determine the effectiveness of stems and chopped citronella (Cymbopogon nardus) in controlling S. oryzae during rice storage. The design used was a Completely Randomized Design (CRD) with eight treatments and three replications. The results showed that the Z5 treatment gave the highest mortality of 14.00%, while the control (KO) only had 3.33%. The highest percentage of damage occurred in KO (59.33%) and the lowest in Z2 (13.00%). The highest population of S. oryzae was found in KO (87.00) and the lowest in Z5 (28.00), indicating the effectiveness of this treatment. It can be concluded that the provision of citronella stems and chopped citronella can significantly reduce the population, mortality and damage to rice caused by Sitophilus oryzae during 40 days of storage.